Headed for the blues a memoir - Škvorecký, Josef 1924-2012 (Ecco Press, 1996)
Jazz, politics, sex, fear, and the humor necessary to survive absurdity provide the backdrop as Skvorecky seamlessly interweaves his own story with those of his friends; particularly that of his childhood friend Prema, whose life stands in stark contrast to Skvorecky's own. Forced to flee the country shortly after the end of World War II for illegally broadcasting from a stolen transmitter, Prema embarks on an itinerant life, wandering as far as Australia, occasionally dropping Skvorecky "Dear Old Buddy" postcards reporting on a life robbed of its home and its promise. Headed for the Blues recounts Czechoslovakia's evolution from Nazi rule to Soviet-dominated communism, from the age of the "exhausted executioners" ("there were so many executions the Ministry asked them to slow down, the executioners are exhausted") to the age of those petty agents of the secret police called fizls ("rhymes with weasels"), a time when friends and neighbors - even family members - informed on one another. As a culture of fear and mistrust grew in the country, the lives of its people were heedlessly tossed about by the winds of politics. Throughout the book there are fascinating digressions on the subject of writing from a master of twentieth-century literature. Skvorecky discusses his own novels, the works of others, the process of writing, and the differences between real life and his highly autobiographical fiction.
Aus dem Tschech. übers.
Keywords: S̆kvorecký, Josef <1924->; Škvorecký, Josef; Škvorecký, Josef -- 1924-2012; Geschichte 1900-2000; Écrivains tchèques - 20e siècle - Biographies; Authors, Czech -- 20th century -- Biography; Autobiografie; Biografie